2005
DOI: 10.1016/j.bbabio.2004.08.009
|View full text |Cite
|
Sign up to set email alerts
|

P700+- and 3P700-induced quenching of the fluorescence at 760 nm in trimeric Photosystem I complexes from the cyanobacterium Arthrospira platensis

Abstract: The 5 K absorption spectrum of Photosystem I (PS I) trimers from Arthrospira platensis (old name: Spirulina platensis) exhibits long-wavelength antenna (exciton) states absorbing at 707 nm (called C707) and at 740 nm (called C740). The lowest energy state (C740) fluoresces around 760 nm (F760) at low temperature. The analysis of the spectral properties (peak position and line width) of the lowest energy transition (C740) as a function of temperature within the linear electron-phonon approximation indicates a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…Because P700 ϩ and the long-lived P700 triplet state quench fluorescence (38), the PS I Chl fluorescence yield is low under our experimental conditions. Similarly, the PS II Chl fluorescence yield is low because P680, the primary donor in the PS II reaction center, primarily remains in the oxidized state during excitation: P680 ϩ , a fluorescence quencher (39), is reduced on the time scale of 10 ns to several microseconds (40), and excitations are expected to arrive at the PS II reaction center 10-1,000 times more frequently.…”
Section: Hyperspectral Imaging Of Intact Synechocystis Cellsmentioning
confidence: 99%
“…Because P700 ϩ and the long-lived P700 triplet state quench fluorescence (38), the PS I Chl fluorescence yield is low under our experimental conditions. Similarly, the PS II Chl fluorescence yield is low because P680, the primary donor in the PS II reaction center, primarily remains in the oxidized state during excitation: P680 ϩ , a fluorescence quencher (39), is reduced on the time scale of 10 ns to several microseconds (40), and excitations are expected to arrive at the PS II reaction center 10-1,000 times more frequently.…”
Section: Hyperspectral Imaging Of Intact Synechocystis Cellsmentioning
confidence: 99%
“…69 No. 11 2004 triplet and the quenching of F760 indicates that P700 triplet quenches the fluorescence of the reddest chloro phyll C740 [58,59].…”
Section: Dissipation Of Excitation Energy In Psi Of Cyanobacteriamentioning
confidence: 99%
“…Previous studies have demonstrated that 'red chlorophylls' with Q y absorption maxima up to 760 nm can be found in several oxygenic photosynthetic organisms (Koehne et al 1999;Schlodder et al 2005;Wilhelm and Jakob 2006). These 'red chlorophylls' are mostly found in light-harvesting complexes, although the formation and function of those 'red chlorophylls' in energy storage is under debate (Melkozernov and Blankenship 2003;Corbet et al 2007).…”
Section: Oxygenic Photosynthesis and Its Physical Limitsmentioning
confidence: 99%